An evolutionary history embedded in amber: reflection of the Mesozoic shift in weevil-dominated (Coleoptera: Curculionoidea) faunas. (27th June 2014) - Peris, David; Davis, Steven R.; Engel, Michael S.; Delclòs, Xavier
Abstract: Three new weevil (Coleoptera: Curculionoidea) species from Cretaceous amber of Spain (early Albian) and France (late Albian–early Cenomanian) are described. Nemonychidae are represented by two Spanish specimens from the El Soplao and San Just deposits and described as Arra legalovi gen. et sp. nov., Caridae are described from one specimen in the Spanish deposit of El Soplao and named as Albicar contriti gen. et sp. nov., and Curculionidae are documented from one specimen embedded in opaque amber from the French deposit of Archingeay and described as Antiquis opaque gen. et sp. nov. These three new species provide valuable information because they appear to reflect, together with the previously described weevils in Cretaceous ambers, the gradual shift in the dominance of particular curculionoid families across the Cretaceous. Propagation phase-contrast X-ray synchrotron microtomography was utilized to obtain high quality 3D images for some fossils and, at the same time, permit a concise description of them.